2002
DOI: 10.1097/00004770-200202000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Matrix Metalloproteinases by Black-Pigmented Bacteroides in Human Pulp and Periodontal Ligament Cell Cultures

Abstract: Matrix metalloproteinases (MMPs) are a group of proteolytic enzymes capable of degrading most components of the extracellular matrix. Recently, evidence has shown that MMPs may play a role in tissue degradation in inflamed dental pulp. To date very little is known regarding the mechanism of extracellular matrix destruction at the site of bacterial infection. The purpose of this study was to determine the effects of the supernatants from Porphyromonas endodontalis and Porphyromonas gingivalis on the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 20 publications
4
49
1
6
Order By: Relevance
“…Bacterial infection is a condition for the development of periapical lesions when it is derived from extensive carious lesions. MMP9 production was enhanced in human pulp and periodontal ligament cells stimulated with endodontic pathogens (23).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Bacterial infection is a condition for the development of periapical lesions when it is derived from extensive carious lesions. MMP9 production was enhanced in human pulp and periodontal ligament cells stimulated with endodontic pathogens (23).…”
Section: Discussionmentioning
confidence: 94%
“…MMP2 modulates many physiological conditions including wound repair and tissue remodeling (22). In physiological condition, MMP2 is expressed by periodontal ligament cells (23) and acts in response to infection, tissue remodeling and injury. In our study, we observed that MMP2 expression was lower in the TLR2 KO mice than in the WT at 42 days.…”
Section: Discussionmentioning
confidence: 99%
“…There are increasing evidences that MMPs are essential enzymes responsible for degradation of extracellular matrix in the pathological condi- 19) . Numerous studies have examined MMPs secreted from periodontal ligament fibroblast [20][21][22] and correlated the level of expression with the invasive ability of the disease 4,6) . Individual osteoblasts, like fibroblasts, are capable of both synthesizing and degrading their respective organic matrices in vivo 23) .…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…It is con-ABSTRACT ceivable that, since the major component of the organic bone matrix is collagen, collagenolytic enzyme, synthesized by osteoblasts, may also participate in the degradation of the mineralized collagen during bone resorption 3) . Matrix metalloproteinases (MMPs) are well known proteolytic enzymes for the degradation of extracellular matrix and this proteolysis is believed to play an essential role in the development and progression of pulpal and periapical inflammation 4) . MMPs, produced by osteoblastlike cells, are likely to be involved in various steps of the bone resorption process 5) .…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 1 more Smart Citation